25.9k views
0 votes
Plz help me thanks

Complete the square to make a perfect square trinomial. Then, write a result as a binomial squared. m^2-13m

m^2-13+ ? =( ? )^2

User Yagiz
by
5.0k points

1 Answer

4 votes

Answer:

Trinomial


m^2 - 13m + (169)/(4)

Binomial squared


(m - (13)/(2))^2

Explanation:

Given


m^2-13m

Required

Make a perfect trinomial

We have:


m^2-13m =

-----------------------------------------------

Take the coefficient of m i.e. -13

Divide by 2 i.e. -13/2

Square i.e. (-13/2)

Add to both sides of the equation

-----------------------------------------------


m^2-13m = becomes


m^2 - 13m + ((-13)/(2))^2 = ((-13)/(2))^2


m^2 - 13m + (169)/(4) = (169)/(4)

Expand


m^2 - (13)/(2)m- (13)/(2)m + (169)/(4) = (169)/(4)

Factorize:


m(m - (13)/(2))- (13)/(2)(m - (13)/(2)) = (169)/(4)

Factor out m - 13/2


(m - (13)/(2))(m - (13)/(2)) = (169)/(4)

Write as square


(m - (13)/(2))^2 = (169)/(4)

Hence, the trinomial is:


m^2 - 13m + (169)/(4)

And the binomial squared is:


(m - (13)/(2))^2

User Leen
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.